A strategic analysis of goals scored in open play in four FIFAWorld Cup football championships between 2002 and 2014 - Smith, R. A.; Lyons, K. (International Journal of Sports Science & Coaching, 2017)
This study analyzed game events leading up to the goals in four FIFAWorld Cups. Three categories of goals are presented: (a) from passing the ball behind the opposing defense or to a player level with the last defender who could either shoot or take the ball forwards or pass to a team mate to score, (b) from in front of the opposing defense or from dribbling past the last line of defense, referred to as 'Other Methods', and (c) from Crosses. The field of play was divided into seven zones to determine the origin of passes for goals in category (a) and (c) and three equal areas lengthwise to determine where possession was regained. The study concludes that the most dominant method of scoring goals in Open Play was from category (a), followed by category (b) and (c). Most goals in category (a) were from passes in the area referred to as Zone 14+ and the majority of goals in all categories came from regained possessions in the middle third. ABSTRACT FROM AUTHOR